Finite element analysis of anchored sheet-pile wall - Wong, Kum Fai. (2009)
For anchored sheet pile walls, the classical method of determining depth of penetration can be done using limit equilibrium. It uses log-spiral graphs to determine the appropriate KAH and KPH values with δ=0.66φ. These values are used for the horizontal pressures, which in turn allow horizontal forces to be determined.